Clavigeritae (Coleoptera, Staphylinidae, Pselaphinae) of the Arabian Peninsula with the description of a new species of Corynotopsis Jeannel, 1951 from Oman - Hlaváč, Peter; Baňař, Petr; Stočes, Dominik (Pensoft Publishers, 2024)
Corynotopsis omanicus sp. nov. of the myrmecophilous supertribe Clavigeritae is described from Oman. The type series was collected at night and the ant host species remains unknown. Corynotopsis scotti Jeannel, 1951 is newly recorded for Yemen, and Commatocerus concinnus Besuchet & Cuccodoro, 2011 for Oman. Lasius Fabricius, 1804 and Lepisiota Santschi, 1926 are, for the first time, determined as hosts of the latter species. The problematic taxonomic status of Corynotopsis scotti is discussed. A distribution map of all Clavigeritae known from the Arabian Peninsula is provided.
Keywords: Articerodes; Commatocerus; new country records; rove beetles; taxonomy